Psychosocial Impact of Postmastectomy Lymphedema Syndrome: Insights From a National Claims Database Analysis of Antidepressant Prescription Fills - Daniel Najafali, BS; Jennifer K. Shah, BA, BS; Thomas M. Johnstone, BS; Justin M. Camacho, MBA; Priscila C. Cevallos, BS, MS; Kometh Thawanyarat, BA; Yelissa Navarro, BS; Rahim S. Nazerali, MD; Clifford C. Sheckter, MD, MS (Plastic and Reconstructive Surgery, Global Open)
Background:. Postmastectomy lymphedema syndrome (PMLS) has been associated with lower quality of life due to symptoms and financial consequences. This study assessed the impact of PMLS on psychosocial well-being using antidepressant fill patterns. We hypothesized that PMLS increased the odds and duration of antidepressant fills. Methods:. Mastectomy encounters in the Merative MarketScan Research Databases, 2007–2022, were extracted using Current Procedural Terminology codes. Among these, patients who developed PMLS and filled antidepressant prescriptions were identified using the International Classification of Diseases, Ninth and Tenth Revision, codes and generic drug names. Univariate and multivariate logistic regression tests were performed for statistical analyses. Results:. Of 300,075 patients meeting criteria (median [interquartile range] age, 52 [45–59] y), 24,753 (8.2%) experienced PMLS. In a multivariate regression, younger age, less recent surgical year, and higher Elixhauser Comorbidity Index scores were associated with heightened odds of PMLS (P < 0.001). In a multivariate regression, PMLS diagnoses increased odds of filling antidepressant prescriptions (26.8% versus 16.5%; odds ratio 1.55; P < 0.001). Time to last postmastectomy antidepressant fill was greater for patients with PMLS (P < 0.001). In a propensity score–matched model of patients with PMLS with and without lymphedema interventions, such interventions did not impact time to last postmastectomy antidepressant fill (P = 0.963). Conclusions:. Patients with PMLS were associated with increased antidepressant fills compared with those without lymphedema. Lymphedema surgery did not impact duration of postmastectomy antidepressant fills. Future studies should evaluate the longitudinal abilities of surgical interventions to ameliorate depression in patients with PMLS.